A função de capital humano : externalidades setoriais - Schumacher, Florian Immanuel (2010)
The aim of this research is to evaluate whether there are knowledge spillover effects in the Brazilian economy, as proposed by Lucas (1988), Romer (1990) and Acemogiu (1996). The spiliover effect is verified in the business services sector, which consists of the following sub-sectors: telecommunications, consuiting services and research. The hypothesis is to verify if the employment by these industries of people educated at the masters levei and above causes a productivity increase in other sectors. We estimate the returns to education in major market sectors using data from the Brazilian household survey PNAID (2008). The result of the proposed conjecture was positive and significant, with an impact of 3% to 4% over the real wage. In additiori, we obtain evidence for the existence of increasing returns to education in Brazii, probably due to the spiilover effect, since these returns are present in greater or lesser degree in ali major sectors of the Braziiian economy.